2015
DOI: 10.4314/sajas.v45i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of chitosan and buckwheat (<i>Fagopyrum esculentum</i>) on the performance and serum lipid profile of broiler chicks

Abstract: This study was conducted to evaluate the effects of different levels of buckwheat (Fagopyrum esculentum) alone or in combination with chitosan, in broiler diets, on the growth, feed intake and serum lipid profile of broilers. Starting as 10-day olds, 144 Cobb 500 broiler chicks were fed six manually prepared diets containing 0%, 10%, 20% or 30% buckwheat, or 10% buckwheat supplemented with 250 mg chitosan or 500 mg chitosan/kg. The trial lasted 32 days. Buckwheat alone or in combination with chitosan had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
6
6
0
Order By: Relevance
“…The findings of our current research are more or less in accordance to the findings of some earlier researchers (Guler et al, 2006;Ziad et al, 2008;Majeed et al, 2010). The current findings and earlier results (Islam et al, 2011;Sayed et al, 2015; suggest that herbal feed additives might be an effective alternative to synthetic antibiotics for the promotion of health and performance of poultry. Several studies have observed that BCS has potential as an alternative to antibiotics and vaccination to improve immunity and to reduce mortality in poultry birds owing to the presence of pharmacologically active constituents such as thymoquinone, dithymoquinone, thymohydroquinone, nigellicine, nigellimine and nigellidine (Abdur-Rehman & Abu- Bakar, 1997;Osman & El-Barody, 1999).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The findings of our current research are more or less in accordance to the findings of some earlier researchers (Guler et al, 2006;Ziad et al, 2008;Majeed et al, 2010). The current findings and earlier results (Islam et al, 2011;Sayed et al, 2015; suggest that herbal feed additives might be an effective alternative to synthetic antibiotics for the promotion of health and performance of poultry. Several studies have observed that BCS has potential as an alternative to antibiotics and vaccination to improve immunity and to reduce mortality in poultry birds owing to the presence of pharmacologically active constituents such as thymoquinone, dithymoquinone, thymohydroquinone, nigellicine, nigellimine and nigellidine (Abdur-Rehman & Abu- Bakar, 1997;Osman & El-Barody, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…In previous studies, the authors observed that supplementation of BWS and BCS powder in diets significantly decreased serum total cholesterol, triglycerides and LDL-cholesterol concentrations, and the population of E. coli in broilers and layers (Islam et al, 2011;Sayed et al, 2015;. The findings of our current research are more or less in accordance to the findings of some earlier researchers (Guler et al, 2006;Ziad et al, 2008;Majeed et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations